DEVELOPMENT OF QUICK-STRENGTH ABILITY OF MIDDLE CLASS (5-6 GRADE) STUDENTS - Abdurakhimov Sardor Dilmurot ugli (Galaxy International Interdisciplinary Research Journal, 2023)
Childhood and youth are an important stage in the development of these speed and quick-power skills. The analysis of sources in the literature shows that one of the important stages of developing speed and quick-power skills of young athletes is the age of 11-12 years. As a result of the systematic implementation of the selected set of special exercises and games, an increase in the speed, agility and strength abilities of the students was found. This special set of exercises and games was held in general secondary school No. 10 of Chirchik city and a high result was achieved.